Experiment research of Al particle's ignition and combustion characteristics of NEPE propellant. Issue 1 (1st February 2022) - Xia, Wenjie; Zhuang, Yuqian; Cai, Wenxiang; Xue, Donglin; Cao, Yanbang; Song, Xiaodong
Abstract: Based on optical photography analysis method, agglomeration process of Al particles at aluminized NEPE propellant's surface, dynamic combustion process after leaving burning surface and the collision under different pressure of N2, were photographed by highspeed camera. MATLAB was used to deal with the images to analyze the size of agglomerated particles. Experiment research results showed that higher pressure was helpful for improving ignition performance and increasing combustion efficiency of the aluminized NEPE propellant. For the agglomeration products, dimension was reduced, size distribution became more uniform, and amount of the mass increased with higher pressure environment.